(untitled) (Journal on studies and research of academic knowledge, 2022)
The work of bibliographic review and study of the case of Encarnacion city aims to study the impact of mobility in the urban environment of the Encarnacion city, for which the descriptive method is uses with the application of closed questions and interviews with people over 18 years who are mobilized, completed with observation, measurement, and participant observation. It is shown that the needs of the population are not being satisfied in the neighborhoods on the periphery of the city, demanding mobility infrastructure to solve them, which exposes the influence the influence factors such as urban planning, location, and the solution of needs on account of services in other areas, generating an impact on the development of the urban environment both through infrastructure as for the mobility itself.